(untitled) (REVUE DES SCIENCES DE LA SANTE, 2026)
the Democratic Republic of Congo (DRC), despite initiatives implemented to improve access to palliative care, medical institutions face challenges such as a shortage of qualified personnel, the absence of systematic educational programs, and limited awareness among healthcare professionals. The University Clinics of Kinshasa (C.U.K), as a leading institution, hold a pivotal role in the development and implementation of continuous training in palliative care, aiming to enhance the quality of care and ensure dignified management for patients with advanced illnesses. The primary objective of this research is to analyze nurses’ perceptions and expectations regarding continuous training in palliative care within the University Clinics of Kinshasa. This study falls within the field of public health, specifically focusing on palliative care. To conduct this research, a descriptive approach employing a qualitative phenomenological methodology was selected. Data collection was carried out through semi-structured individual interviews with participants. The findings revealed a strong need for continuous training in palliative care, alongside significant challenges in practice, such as insufficient resources for both patients and caregivers. It is essential to ensure institutional and financial support for palliative care, improve accessibility to training, and strengthen interdisciplinary teams to enhance the quality of care in this critical domain.